2018
DOI: 10.1007/s11104-018-3656-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic framework to link root growth models with weather and soil physical properties, including example applications to soybean growth in Brazil

Abstract: 2018). Mechanistic framework to link root growth models with weather and soil physical properties, including example applications to soybean growth in Brazil. Plant and Soil,, 67-92. https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 82 publications
0
57
0
5
Order By: Relevance
“…Under this condition, tractor traffic intensification caused soil compaction states not harmful to soybean plants, maintaining satisfactory physical and hydraulic conditions to the crop performance (Moraes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Under this condition, tractor traffic intensification caused soil compaction states not harmful to soybean plants, maintaining satisfactory physical and hydraulic conditions to the crop performance (Moraes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These models, however, are usually based on simplifying assumptions such as a uniform root distribution and homogeneous root water uptake in lateral soil horizons. The effect of soil structure is thereby at best taken into account indirectly via stress functions on root elongation (e.g., de Moraes et al, 2018; Gaiser et al, 2013). If the impact of biopores on model input parameters such as root length density development, root system hydraulic conductance, and the relative distribution of root water uptake is known, the effects of structured soil can be taken into account more accurately.…”
mentioning
confidence: 99%
“…Consequently the structural quality of the soil showed that an increase in C was positively associated with the reduction in ρ b (Figure 5). However, taking into consideration the high values of ρ b and reduced macroporosity, and values observed in the pasture areas (Table 3), these benefits to the soil structure provided by the successive use of LSM are still very limited and are insufficient to fully alleviate limiting conditions induced by soil compaction to ensure suitable root growth (Moraes et al, 2018).…”
Section: Impacts Of Lsm Applications On Soil Physical Attributesmentioning
confidence: 99%